STRATEGI BAURAN PEMASARAN UNTUK MEMPERTAHANKAN EKSISTENSI USAHA PASCA PENDEMI COVID 19 PADA CAFE KOPIDARAT KABUPATEN BANGKALAN - Nur Rizky Tera Odiana; Manah Tarman; Aulia Dawam (JURNAL LENTERA BISNIS, 2023)
The research aims to describe the flow of the marketing mix applied to Cafe Kopidarat for various businesses during the Covid 19 pandemic. Research methods use Data collection is carried out through documentation of triagulation (combination) of the results of interviews, observations and data analysis techniques, namely data reduction, data presentation, and conclusion verification This type of research is using descriptive qualitative. Cafe Kopidarat's research results show that it has implemented a marketing mix strategy adapted to the post-Covid 19 pandemic because it has to implement health protocols, follow government regulations and advice from PPKM. The obstacles experienced by Cafe Kopidarat are that sales transactions have decreased drastically in post-Covid 19, consumers are decreasing, promotions are still not optimal in post-covid 19.Keywords: Marketing Mix, business existence, Covid 19.